2019
DOI: 10.1589/jpts.31.149
|View full text |Cite
|
Sign up to set email alerts
|

A study on the sleep quality, pain, and instrumental activities of daily living of outpatients with chronic stroke

Abstract: [Purpose] The purpose of this study is to examine the sleep quality, pain, and instrumental activities of daily living (IADL) of outpatients with chronic stroke, and to examine their correlation. [Participants and Methods] This study was conducted on 42 outpatients with chronic stroke, and data on their sleep quality, pain, and instrumental activities of daily living were collected and analyzed using the survey measurement tools. [Results] The analysis shows significant correlations among the sleep quality, pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
4
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 16 publications
(17 reference statements)
0
4
1
Order By: Relevance
“…We were unable to examine the correlation between the mRS and 0–10 NPRS in our dataset due to unavailability of corresponding datapoints, but previous work reported a weak relationship between pain and the mRS ( 25–27 ). We observed a correlation of −0.097 between the BI and the 0–10 NPRS; considerably weaker than previous work describing associations between the 0–10 NPRS and the Korean Instrumental Activities of Daily Living (K-IADL), reporting a correlation of 0.374 ( 28 ). The capture of pain by EQ-5D-3L was not improved by considering participants’ ability to care for themselves, complete ADLs, presence of anxiety/depression or overall health state.…”
Section: Discussioncontrasting
confidence: 99%
“…We were unable to examine the correlation between the mRS and 0–10 NPRS in our dataset due to unavailability of corresponding datapoints, but previous work reported a weak relationship between pain and the mRS ( 25–27 ). We observed a correlation of −0.097 between the BI and the 0–10 NPRS; considerably weaker than previous work describing associations between the 0–10 NPRS and the Korean Instrumental Activities of Daily Living (K-IADL), reporting a correlation of 0.374 ( 28 ). The capture of pain by EQ-5D-3L was not improved by considering participants’ ability to care for themselves, complete ADLs, presence of anxiety/depression or overall health state.…”
Section: Discussioncontrasting
confidence: 99%
“…Although no previous studies have specifically examined the relationship between motor impairment and sleep disruption measures at the chronic stage of stroke, generally it has been reported that people with more severe stroke self-report worse sleep quality. 14 , 15 , 34 The lack of findings here suggests that the relationships found previously may be influenced by other factors that contribute to stroke severity scores, over and above motor impairment. Information on stroke severity (eg clinical stroke severity scores or lesion volumes) was not available or collected in the current study and therefore we are unable to test this possibility directly.…”
Section: Discussionmentioning
confidence: 59%
“…There is some indication that sleep quality may relate to stroke outcomes, using broad measures of independence in activities of daily living 14 or disability. 15 , 16 We previously demonstrated that sleep disruption during inpatient rehabilitation from stroke and brain injury is associated with poorer motor outcomes 17 and hypothesise that this may be, at least in part, due to impaired consolidation of motor learning underlying motor recovery.…”
Section: Introductionmentioning
confidence: 99%
“…1,[9][10][11] Consequently, a reduction in physical functioning, psychological well-being, self-care, activities of daily living, ability to work, and interpersonal relationships has been reported to be associated with reduced sleep quality in adolescents and young adults. [3][4][5][6][7]10,[12][13][14][15][16][17] Emphasizing the importance of sleep quality and including sleep assessment as a major part of the routine clinical practice are necessary. Therefore, a better understanding of sleep quality assessment tools can help in the identification and management of sleep problems before the patients suffer the long-term consequences associated with poor sleep.…”
Section: Introductionmentioning
confidence: 99%